Hematopoietic stem cell transplantation in patient with DOCK8 deficiency: Ukrainian experience - A.M. Hilfanova; D.V. Zabara; O.V. Lysytsya; A.V. Volkova (Group of Companies Med Expert, LLC, 2023)
Dedicator of Cytokinesis 8 (DOCK8) deficiency is a combined immunodeficiency that exemplifies the broad clinical features of primary immunodeficiencies (PIDs), extending beyond recurrent infections including atopy, autoimmunity, and cancer. Purpose - to describe the natural course of hyper-IgE syndrome (HIES) disease in an 8-year-old boy and his path to diagnosis, as well as our first local history of conservative treatment for 6 months. In particular, we describe the effectiveness of omalizumab, and the application of allogeneic hematopoietic stem cell transplantation with follow-up. Clinical case. The 8-year-old boy presented with severe eczema and an involvement of the whole surface of the body. Infectious syndrome manifested from the age of 4 months in a form of recurrent respiratory infections. Over the next few years, the child suffered from life-threatening infections with high serum IgE (>3000 IU/ml). The examination revealed a cushingoid constitution, flat-valgus feet, and dysmorphic features. Therefore, HIES was suspected. Genetic studies have confirmed the diagnosis by detecting a pathogenic homozygous mutation in the DOCK8 gene (Deletion Exons 2-46). We decided to use a humanized monoclonal anti-IgE antibody (off-label) to control the skin syndrome rather than systemic steroids. A significant improvement in skin condition, a decrease in eosinophils, and IgE were observed. Allogeneic stem cell transplantation of hematopoietic cells (HSCT) derived from peripheral blood of an human leukocyte antigen (HLA) - identical sibling donor was performed. The donor had a pathogenic mutation identical to the recipient in the DOCK8 gene but in a heterozygous state. Our data and treatment approach may be clinically useful as a diagnostic and treatment approach to HIES. The research was carried out in accordance with the principles of the Helsinki Declaration. The informed consent of the patient was obtained for conducting the studies No conflict of interests was declared by the authors.